1963
DOI: 10.5254/1.3539546
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Unsaturated Monomers to Rubber and Similar Polymers

Abstract: The addition of different ethylene monomers to polyisoprene was studied in order to throw a light on reaction mechanisms and structures of reagents. It was attempted, during the planned transformations, to maintain as best as possible the shapes and sizes of initial macromolecules, upon which rests the property of high elasticity. For this purpose, it was decided to avoid grafting reactions, as well as any reactions affecting the nature of the polyisoprenic chain, e.g., scission, cross-linking, and cyclization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

1969
1969
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…3 From Arrhenius plots, Benn et al 14 estimated the activation energy for several alk-1-enes and for cis-and trans-dec-5-ene, to be 90, 76, and 77 KJ/mol, respectively. Rondestvedt and Wark 15 estimated the activation energy for the Alder Ene reaction between maleic anhydride and allylbenzene (84 KJ/mol) to be in the range of those determined by Benn et al 14 The presence of a free radical inhibitor had no effect on the rate of reaction; 14,16 however, in its absence and in the presence of air, maleic anhydride-alkene copolymer formation was observed.…”
Section: Introductionmentioning
confidence: 99%
“…3 From Arrhenius plots, Benn et al 14 estimated the activation energy for several alk-1-enes and for cis-and trans-dec-5-ene, to be 90, 76, and 77 KJ/mol, respectively. Rondestvedt and Wark 15 estimated the activation energy for the Alder Ene reaction between maleic anhydride and allylbenzene (84 KJ/mol) to be in the range of those determined by Benn et al 14 The presence of a free radical inhibitor had no effect on the rate of reaction; 14,16 however, in its absence and in the presence of air, maleic anhydride-alkene copolymer formation was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Though the maleic anhydride is purported and mechanistically favoured an Diels-Alder reaction (Alder et al 1943) in the methylene/allylic double carbon bonds (> C = C <) as reported in the classical chemical reactions (Baraboim & Popov 1963), and also by Pinazzi (Pinazzi et al 1963), andFarmer (1942)in natural rubber, while Loo (1985) reported that it is possible that the dibasic acids could be used to open the epoxide ring and also used as crosslink sites, or the dibasic acids used to crosslink in the non-sulphur accelerated curing system.…”
Section: Chemical Reaction Mechanism That Possibly Enhances the Propementioning
confidence: 97%
“…O anidrido maleico (AM) tem sido utilizado para modificar diversos polímeros, como polietilenos [5,6] , polipropileno [7,8] , EPDM [9] , EPR [10] , eicosano e esqualano [11] e elastômeros [12] . A enxertia de AM pode ser realizada por diferentes métodos, como em solução [7] , em estado fundido [13] , em suspensão [12] e em estado sólido [14] .…”
Section: Influência Da Estrutura De Diferentesunclassified